Exam AZ-104 Microsoft Azure Administrator (video) (Microsoft Press, 2022)
7+ Hours of Video Instruction This course will help an IT professional learn about common Azure services and prepare for the Exam AZ-104: Microsoft Azure Administrator. Overview Cloud Skills are becoming an important part of any IT professional's resume. The Microsoft Azure Administrator Associate certification proves foundational IT skills in creating and managing workloads in the Microsoft Azure cloud. This course is designed to help you pass Exam AZ-104: Microsoft Azure Administrator and earn the Microsoft Azure Administrator Associate certification. All the skills measured on the exam are covered in this course including: Manage Azure identities and governance Implement and manage storage Deploy and manage Azure compute resources Configure and manage virtual networking Monitor and back up Azure resources Combining his experience as Microsoft Trainer for more than 25 years and familiarity of Microsoft solutions from running his own business designing custom software solutions, Ray will efficiently and effectively help you navigate through the exam objectives as you prepare for your exam. Learn How To Manage user identities in Azure Create and manage Infrastructure-as-a-Service resources in Azure Create and manage Platform-as-a-Service resources in Azure Create and manage file data in Azure Learn about key Azure resources and workloads Who Should Take This Course Any student pursuing the Microsoft Azure Administrator certification Any student who wants to learn about foundational services in Azure Course Requirements A basic knowledge of IT administration concepts such as virtual machines, networking, and user account security is strongly encouraged. A basic knowledge of Azure is recommended, but not required. About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video. Video Lessons are available for download for offline viewing within the streaming format. Look for the green arrow in each lesson.